The curious case of missing defaults - Carmen M. Reinhart (American Enterprise Institute (AEI), 2019)
In a recent paper on the long coincident behavior of international capital flows, commodity prices, and interest rates in global financial centers, Reinhart, Reinhart, and Trebesch (2016 and 2017) discovered the curious case of missing defaults. Despite the drying up of global capital flows and a sharp fall in commodity prices from 2012 to 2016, sovereign defaults in emerging market and developing economies did not spike higher as predicted by the record of the prior two hundred years. An important new dimension in the latest global capital flow cycle is the surge in Chinese loans to developing countries, notably low-income commodity producers since the early 2000s. A key driver of China's overseas lending boom is its significantly larger global footprint, which expanded at a record clip and helped stabilize global trade especially since the global financial crisis. Furthermore, Chinese official ambition to become a global power led to large official flows to support development projects and other purposes. The key question for policy makers and investors is whether these missing defaults are deferred or defused. There is also evidence to suggest that many developing borrowers are already encountering problems in servicing their recent debts to China (sovereign defaults are mis measured). This analysis aims to shed light into what is currently one of the most opaque issues in global finance. For researchers a key question is whether this new source of support changes the empirical determinants of global capital flows.
Keywords: A; 330; Financial markets; finance; global